2017
DOI: 10.1007/s00449-017-1881-0
|View full text |Cite
|
Sign up to set email alerts
|

Organic acid pretreatment of oil palm trunk: effect on enzymatic saccharification and ethanol production

Abstract: Effective lignocellulosic biomass saccharification is one of the crucial requirements of biofuel production via fermentation process. Organic acid pretreatments have been gained much interests as one of the high potential methods for promoting enzymatic saccharification of lignocellulosic materials due to their lower hazardous properties and lower production of inhibitory by-products of fermentation than typical chemical pretreatment methods. In this study, three organic acids, including acetic acid, oxalic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…3). The efficiency of cellulase enzyme was compared based on the hydrolysis product in the form of reducing sugar [22][23]. Testing with CMC substrate, the reducing sugars obtained from a total 32 samples were ranged from 0.51-4.35 mg/mL (Fig.…”
Section: Composition Of Cassava Pulpmentioning
confidence: 99%
“…3). The efficiency of cellulase enzyme was compared based on the hydrolysis product in the form of reducing sugar [22][23]. Testing with CMC substrate, the reducing sugars obtained from a total 32 samples were ranged from 0.51-4.35 mg/mL (Fig.…”
Section: Composition Of Cassava Pulpmentioning
confidence: 99%
“…After 24 hours of fermentation, glucose and xylose could be almost completely metabolized and the ethanol concentration was 12.59 g/L, corresponding to an ethanol yield of 73.6%. It has been reported that oil palm trunk treated with different organic acid were enzymatically hydrolyzed and used as substrate for ethanol fermentation, citric acid was the most efficient organic acid for pretreatment to enhance ethanol production compared to acetic acid and oxalic acid [25].…”
Section: Enzymatic Hydrolysis and Ethanol Productionmentioning
confidence: 99%
“…These studies showed that dicarboxylic organic acids can hydrolyze β-1,4 bonds more selectively than sulfuric acid [24]. Except to these dicarboxylic acids, citric acid was also used to pretreatment of oil palm trunk [25]. It also demonstrated a similar good performance of hemicellulose and lignin removal from oil palm trunk.…”
Section: Introductionmentioning
confidence: 99%
“…There were reports that OPF biomass was able to enhance enzymatic hydrolysis with the proper pre-treatment approach [4]. Other parts of the oil palm waste which were utilized for biorefinery includes empty fruit bunch and oil palm trunk [5,6]. OPF was discovered to be able to produce renewable sugars simply by pressing the fresh OPF to obtain the juice or sap [7].…”
Section: Introductionmentioning
confidence: 99%